2015
DOI: 10.1007/s12524-014-0437-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Multiple Scattering of Radiation amongst End Members in a Mixed Pixel of Hyperspectral Data for Identification of Mangrove Species in a Mixed Stand

Abstract: The Sunderban Biosphere Reserve of southern West Bengal, India offers an ideal locale where Hyperspectral Remote Sensing may be applied for mapping diverse range of mangrove plantations that are unique to this pristine ecological system. This delta is characterized by both 'pure' and 'mixed' mangrove forest patches where photons interact with multiple species within the instantaneous field of view of the hyperspectral sensor, and multiple scattering between the vegetation canopies becomes significantly nonline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Most studies on mangrove species classification were conducted using pixel-based methods such as spectral angle mapper (SAM) [45,46], maximum likelihood classification (MLC) [7,8,46], and spectral unmixing [47][48][49], or object-based methods, such as nearest neighbor (NN) [20,21], random forest (RF) [50], and support vector machine (SVM) [14,51,52]. Previous studies have shown that the object-based methods generally outperformed the pixel-based methods for mangrove species classification, particularly with high-resolution hyperspectral images [21,[53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on mangrove species classification were conducted using pixel-based methods such as spectral angle mapper (SAM) [45,46], maximum likelihood classification (MLC) [7,8,46], and spectral unmixing [47][48][49], or object-based methods, such as nearest neighbor (NN) [20,21], random forest (RF) [50], and support vector machine (SVM) [14,51,52]. Previous studies have shown that the object-based methods generally outperformed the pixel-based methods for mangrove species classification, particularly with high-resolution hyperspectral images [21,[53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…In linear spectral unmixing, assuming y as the intensity value of each pixel in the hyperion image and m r as the matrix representing the signature of pure mangrove species identified by NFINDR, the fractional abundance a r is estimated using the equation However, in mixed natural forests like the Sunderban nonlinear models that consider radiation interaction between several objects within a pixel area and manifold scattering between the plant canopies are likely to provide precise end-member detection of species and their abundance estimation. In bilinear models, it is implicit that the radiation incident on each mangrove end-member suffers reflections with other mangrove species existing in close vicinity 31 . The radiation reflected from the initial end-member is reflected once more by the subsequent end-member and then intercepted by the satellite sensor.…”
Section: Nonlinear Modelmentioning
confidence: 99%
“…Extensive research works have been done in the literature to address spectrum unmixing problems based on linear and nonlinear approaches. Nonlinear methods can simulate physical phenomena well, so they can bring better separation or unmixing performance for some applications [11]. Besides, nonlinear methods are usually associated with complex mathematical representations and are applicable to limited applications [12].…”
Section: Introductionmentioning
confidence: 99%